Employability of financial management graduates of a state university in Albay Province - Lustan, Julie Ann M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
With the challenges of unemployment and underemployment, higher education institutions should make sure that they are producing students who are employable. Previous literatures provided some of the determine employability of graduates. In the present study, the results show that the graduates of the BSBA major in Financial Management program are hired within six months after graduation. They are also hired relevant to their specialization. Correlation results shows that most positive characteristics were negatively associated with job relevance, which may indicate trade-offs in career outcomes.